2017
DOI: 10.1155/2017/8539294
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of IL-6, TNF-α, and MCP-1 in Respiratory Viral Infection in Acute Exacerbations of Chronic Obstructive Pulmonary Disease

Abstract: Viral infection is a common trigger for acute exacerbations of chronic obstructive pulmonary disease (AECOPD). The aim of this study is to investigate the expression of cytokines in AECOPD. Patients with AECOPD requiring hospitalization were recruited. Meanwhile healthy volunteers of similar age that accepted routine check-ups and showed no clinical symptoms of inflammatory diseases were also recruited. Induced sputum and serum were collected. Induced sputum of participants was processed and tested for thirtee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 44 publications
(43 reference statements)
1
33
2
Order By: Relevance
“…In addition, an in vivo study in the Friend retrovirus (FV) mouse model showed that IL-6 blockage can reduce viral loads and enhance virus-specific CD8+ T-cell immunity [23]. These findings supported a hypothesis that rapid production of IL-6 might be a possible mechanism leading to the deleterious clinical manifestations in viral pathogenesis [24]. Recently published researches on the clinical characteristics of severe patients with SARS-CoV-2 infection showed that IL-6 was significantly elevated especially in those ICU patients, which caused excessive activated immune response [25,26,27,28,29].…”
Section: Cvl218 Inhibits Il-6 Production In Pbmcs Induced By Cpg-odn mentioning
confidence: 79%
“…In addition, an in vivo study in the Friend retrovirus (FV) mouse model showed that IL-6 blockage can reduce viral loads and enhance virus-specific CD8+ T-cell immunity [23]. These findings supported a hypothesis that rapid production of IL-6 might be a possible mechanism leading to the deleterious clinical manifestations in viral pathogenesis [24]. Recently published researches on the clinical characteristics of severe patients with SARS-CoV-2 infection showed that IL-6 was significantly elevated especially in those ICU patients, which caused excessive activated immune response [25,26,27,28,29].…”
Section: Cvl218 Inhibits Il-6 Production In Pbmcs Induced By Cpg-odn mentioning
confidence: 79%
“…Intratracheal injection of endotoxin, inhalation of tobacco smog combined with lipopolysaccharide (LPS) injection, single tobacco smog instillation or LPS injection are typical procedures to produce a COPD model, which is physiologically similar to human COPD [ 13 ]. LPS could trigger tumor necrosis factor (TNF)-α, interleukin (IL)-8, and IL-10 expression [ 10 , 14 ]. In this study, COPD was successfully produced by intratracheal injection of endotoxin in combination with smoke exposure in rats.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] T cells and T-helper-17 cells demonstrate strong associations with inflammatory cascade in COPD, [ 12 , 13 ] in which inflammatory cytokines are crucial in the early stage, such as tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and interleukin-8 (IL-8), after the release of which the inflammatory cells are concentrated in the site of inflammation to mediate the immune responses. [ 14 , 15 ] Therefore, our study aimed to investigate the predicting value of miR-146a/b for acute exacerbation chronic obstructive pulmonary disease (AECOPD) and stable COPD, and to explore their associations with inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%